Humanitarian supply chain: an analysis of response operations to natural disasters - Costa, Sergio Ricardo Argollo da; Bandeira, Renata Albergaria M.; Mello, Luiz Carlos Brasil B.; Campos, Vânia Barcellos G. (European Journal of Transport and Infrastructure Research, 2014)
This paper presents an analysis of the logistics processes adopted in response to six major natural disasters that occurred in the last decade: (i) the Mozambique flooding in 2000, (ii) the Pakistan earthquake in 2005, (iii) the Indian Ocean tsunami in 2006, (iv) the earthquake in Haiti in 2010, (v) the flood and landslide in the mountainous region of Rio de Janeiro, Brazil in 2010, and (vi) the earthquake and tsunami in Japan in 2011. Through the analysis of secondary data, the main practices, problems and challenges in these post-disaster humanitarian operations are identified. This study aims to understand the environment and circumstances in which these humanitarian operations occurred, assessing the main constraints encountered and the approaches adopted to ensure the supply of relief to victims of natural disasters. Finally, suggestions are proposed in order to improve the efficiency and success rate of the logistics process in other humanitarian response operations.